CD4 T Helper Cells Instruct Lymphopenia-Induced Memory-Like CD8 T Cells for Control of Acute LCMV Infection - Schmitt, Michaela; Sitte, Selina; Vöhringer, David (Frontiers in Immunology, 2016)
Lymphopenic conditions lead to expansion of memory-like T cells (TML), which develop from naïve T cells by spontaneous proliferation. TML cells are often increased in the elderly population, AIDS patients, and patients recovering from radio- or chemotherapy. At present, it is unclear whether TML cells can efficiently respond to foreign antigen and participate in antiviral immunity. To address this question, we analyzed the immune response during acute low-dose infection with lymphocytic choriomeningitis virus-WE in T cell lymphopenic CD4Cre/R-diphtheria toxin alpha (DTA) mice in which most peripheral T cells show a TML phenotype. On day 8 after infection, the total number of effector T cells and polyfunctional IFN-? and TNF-? producing CD8 T cells were three- to fivefold reduced in CD4Cre/R-DTA mice as compared to controls. Viral clearance and the humoral immune response were severely impaired in CD4Cre/R-DTA mice although CTLs efficiently killed transferred target cells in vivo. Transfer of naïve CD4 T cells but not anti-PD-L1 blockade restored the expansion of antigen-specific polyfunctional CD8 T cells and resulted in lower viral titers. This finding indicates that under lymphopenic conditions endogenous CD4 TML cell lack the capacity to promote expansion of CTLs. However, CD8 TML cells retain sufficient functional plasticity to participate in antiviral immunity in the presence of appropriate help by fully functional CD4 T cells. This capacity might be exploited to develop treatments for improvement of CD8 T cell functions under various clinical settings of lymphopenia.
EVALuna2:25884

The B-cell antigen receptor of IgE-switched plasma cells regulates memory IgE responses - Schmitt, Michaela; Lutz, Johannes; Haase, Paul; Bösl, Michael R.; Wienands, Jürgen; Engels, Niklas; Vöhringer, David (Journal of Allergy and Clinical Immunology, 2020)
Background: Allergic inflammation is driven by IgE-producing plasma cells (PCs), which are required for IgE-mediated activation of mast cells and basophils. Repeated antigen encounter elicits a memory IgE response with elevated serum IgE titers and accumulation of IgE-producing PCs. However, the cellular compartment and molecular signals that underlie the immunologic memory of IgE responses remain unclear. Objective: With this study we aimed at clarifying whether inactivation of the cytoplasmic immunoglobulin tail tyrosine (ITT) motif in transmembrane IgE (mIgE) impairs the memory IgE response in mice. Methods: We generated mice with an inactivated mIgE-ITT motif and analyzed serum IgE levels as well as the generation of IgE-producing germinal center B cells and PCs subsequent to primary and secondary infection with helminths. In vitro cultures were used to study the mIgE-ITT–controlled expression of mIgE on the surface of PCs. Systemic mast cell activation was determined by serum Mcpt1 ELISA in response to ovalbumin challenge. Results: mIgE-ITT–mutant mice showed an impaired memory IgE response subsequent to helminth infection. Furthermore, sensitization and challenge of mIgE-ITT–mutant mice with ovalbumin resulted in diminished serum IgE titers and reduced mast cell activation. The mIgE-ITT motif was required for optimal cell surface expression of mIgE B-cell antigen receptors but not for intracellular IgE expression in PCs. Conclusion: These results indicate that the mIgE B-cell antigen receptor plays a critical role in establishing or maintaining the population of IgE-producing PCs during memory IgE responses.
CRIS-Team Scopus Importer:2020-04-14
Keywords: Allergy; B-cell receptor; helminths; IgE; plasma cells

The Extracellular Domains of IgG1 and T Cell-Derived IL-4/IL-13 Are Critical for the Polyclonal Memory IgE Response In Vivo - Turqueti-Neves, Adriana; Otte, Manuel; Schwartz, Christian; Schmitt, Michaela; Lindner, Cornelia; Pabst, Oliver; Yu, Philipp; Vöhringer, David (Plos Biology, 2015)
IgE-mediated activation of mast cells and basophils contributes to protective immunity against helminths but also causes allergic responses. The development and persistence of IgE responses are poorly understood, which is in part due to the low number of IgE-producing cells. Here, we used next generation sequencing to uncover a striking overlap between the IgE and IgG1 repertoires in helminth-infected or OVA/alum-immunized wild-type BALB/c mice. The memory IgE response after secondary infection induced a strong increase of IgE+ plasma cells in spleen and lymph nodes. In contrast, germinal center B cells did not increase during secondary infection. Unexpectedly, the memory IgE response was lost in mice where the extracellular part of IgG1 had been replaced with IgE sequences. Adoptive transfer studies revealed that IgG1+ B cells were required and sufficient to constitute the memory IgE response in recipient mice. T cell-derived IL-4/IL-13 was required for the memory IgE response but not for expansion of B cells from memory mice. Together, our results reveal a close relationship between the IgE and IgG1 repertoires in vivo and demonstrate that the memory IgE response is mainly conserved at the level of memory IgG1+ B cells. Therefore, targeting the generation and survival of allergen-specific IgG1+ B cells could lead to development of new therapeutic strategies to treat chronic allergic disorders.
EVALuna2:25871